A Comparative Assessment of ACCESS Auditor’s Manual and ISO 9001:2015 Standards in the Perspective of Training on ISO 9001 to Cooperative Staff and Board Members - Timsina, Tatwa P (Journal of Advanced Academic Research, 2021)
Cooperatives are people-centred enterprises owned, controlled and run by and for their members to realise their common economic, social, and cultural needs and aspirations. For the proper functioning of the cooperative, various tools such as ACCESS are used. ISO 9001 and similar standards are used for the proper management of the particular organisation. Both the approaches follow different sets of criteria to assess the level of organisation, but there are many similarities between them. They have focused on achieving sustainability and prosperity of the organisation by implementing such criteria in the organisation. This article has aimed to reveal such similarities and dissimilarities and proposed the way of implementing them in a holistic way.